High-Electron-Mobility SiGe on Sapphire Substrate for Fast Chipsets - Hyun Jung Kim; Yeonjoon Park; Hyung Bin Bae; Sang H. Choi (Advances in Condensed Matter Physics)
High-quality strain-relaxed SiGe films with a low twin defect density, high electron mobility, and smooth surface are critical for device fabrication to achieve designed performance. The mobilities of SiGe can be a few times higher than those of silicon due to the content of high carrier mobilities of germanium (p-type Si: 430 cm2/V·s, p-type Ge: 2200 cm2/V·s, n-type Si: 1300 cm2/V·s, and n-type Ge: 3000 cm2/V·s at 1016 per cm3 doping density). Therefore, radio frequency devices which are made with rhombohedral SiGe on c-plane sapphire can potentially run a few times faster than RF devices on SOS wafers. NASA Langley has successfully grown highly ordered single crystal rhombohedral epitaxy using an atomic alignment of the [111] direction of cubic SiGe on top of the [0001] direction of the sapphire basal plane. Several samples of rhombohedrally grown SiGe on c-plane sapphire show high percentage of a single crystalline over 95% to 99.5%. The electron mobilities of the tested samples are between those of single crystals Si and Ge. The measured electron mobility of 95% single crystal SiGe was 1538 cm2/V·s which is between 350 cm2/V·s (Si) and 1550 cm2/V·s (Ge) at 6 × 1017/cm3 doping concentration.